Genetic interactions reveal the evolutionary trajectories of duplicate genes - Benjamin VanderSluis; Jeremy Bellay; Gabriel Musso; Michael Costanzo; Balázs Papp; Franco J Vizeacoumar; Anastasia Baryshnikova; Brenda Andrews; Charles Boone; Chad L Myers (Molecular Systems Biology)
Abstract The characterization of functional redundancy and divergence between duplicate genes is an important step in understanding the evolution of genetic systems. Large‐scale genetic network analysis in Saccharomyces cerevisiae provides a powerful perspective for addressing these questions through quantitative measurements of genetic interactions between pairs of duplicated genes, and more generally, through the study of genome‐wide genetic interaction profiles associated with duplicated genes. We show that duplicate genes exhibit fewer genetic interactions than other genes because they tend to buffer one another functionally, whereas observed interactions are non‐overlapping and reflect their divergent roles. We also show that duplicate gene pairs are highly imbalanced in their number of genetic interactions with other genes, a pattern that appears to result from asymmetric evolution, such that one duplicate evolves or degrades faster than the other and often becomes functionally or conditionally specialized. The differences in genetic interactions are predictive of differences in several other evolutionary and physiological properties of duplicate pairs.